EKSPLORASI MULTIKULTURAL MELALUI PENGALAMAN GURU AGAMA ISLAM DALAM MENGHADAPI TANTANGAN GLOBAL - Rohman, Miftakhul; Hanna Auliya; Feri Hardiansyah (Pascasarjana Universitas Al-Qolam Malang, 2025)
Muslim society is faced with various problems, one of which is global challenges. Religious education is the main milestone for Muslims in understanding Islam as a whole, so here the role of religious education teachers is very important. After the Covid-19 pandemic, a new culture of multicultural society was created with the presence of technology as the main solution to the problem of Islamic education. So in this research we formulate the global challenges faced by multicultural society and how multicultural exploration through Islamic Religious Education Teachers can be done in facing global challenges. The results of this research illustrate that technology plays an active role in shaping the culture of a multicultural society and this is practiced directly by Islamic Religious Educators. They use various social media such as YouTube, Google Met and so on as a means of learning without reducing the substance of Islamic Religious Education material.